Về việc thiết kế một trình biên dịch ngôn ngữ C - Cong, Nguyen Chi; Hai, Nguyen Viet; Lien, Doan Ngoc (Journal of Computer Science and Cybernetics, 2018)
Based on their experiences of writing a Pascal compiler and of interfacing OS9/68K (an UNIX – like operating system) with MS-DOS the authors pointed out a method of designing and implementing a C compuletor MC 68000) as the following: 1) In Microsoft C under MS-DOS creat a program forcrosscompiling the C sources to obtain their objects in MC68000 code. 2) Under MC-DOS use the excutable program for computing his source by himself to get a program in MC68000 code. 3) Under OS9/68K make the wanted compuler executable (from the object code) and compatible with OS9 file format.